Human Capital and Ethnic Self-Identification of Migrants - Laura Zimmermann; Liliya Gataullina; Amelie F. Constant; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
The paper investigates the role of human capital for migrants' ethnic ties towards their home and host countries. Pre-migration characteristics dominate ethnic selfidentification. Human capital acquired in the host country does not affect the attachment to the receiving country.
Keywords: J15; F22; Z10; J24; J16; 330; Ethnic self-identification; first-generation migrants; gender; ethnicity; human capital; Migranten; Humankapital; Ethnische Beziehungen; Soziale Integration; Deutschland